Exogenous Endophthalmitis Caused by Enterococcus casseliflavus: A Case Report and Discussion Regarding Treatment of Intraocular Infection with Vancomycin-Resistant Enterococci - Byron M Berenger; Shobhana Kulkarni; Brad J Hinz; Sarah E Forgie MD (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Endophthalmitis caused by enterococci is rare, and cases involving vancomycin-resistant enterococci are even more so. Due to the poor bioavailability of many antibiotics in the vitreous chamber, special considerations are required when choosing antibiotics to treat these infections. The authors report the first case of exogenous endophthalmitis caused by Enterococcus casseliflavus via the unique mechanism of high-velocity water stream trauma from a toy water gun.